Untargeted metabolomics and DNA barcoding for discrimination of Phyllanthus species. (12th June 2021) - Kiran, Kodsara Ramachandra; Swathy, Puthanvila Surendrababu; Paul, Bobby; Shama Prasada, Kabekkodu; Radhakrishna Rao, Mattu; Joshi, Manjunath B.; Rai, Padmalatha S.; Satyamoorthy, Kapaettu; Muthusamy, Annamalai
Abstract: Ethnopharmacological relevance: Phyllanthus species is extensively cultivated and used as edible fruits and herbal drugs. The Phyllanthus species are used extensively as ethnopharmacologically important materials in several countries, especially in Asia. Various Phyllanthus species are broadly used in the Ayurvedic system of medicine and deliberated as bitter, astringent, stomachic, diuretic, febrifuge, deobstruent, and antiseptic, and used for the treatment of digestive, genitourinary, respiratory, skin diseases, hepatopathy, jaundice, and renal calculus in India. Precise authentification of Phyllanthus species is a challenge due to morphological similarities and is important to avoid adulteration found in herbal drugs. Hence, there is a need to establish comprehensive methods for the identification of Phyllanthus species. Aim of the study: In this study, we attempted to integrate untargeted metabolomics to identify species-specific metabolites with traditional phylogenetic analysis for identification and discrimination of nine Phyllanthus species. Materials and methods: Phyllanthus species such as P. acidus, P. amarus, P. debilis, P. emblica, P. virgatus, P. urinaria, P. lawii, P. myrtifolius, and P. reticulatus were collected. The liquid chromatography coupled mass spectrometry (LC-MS) was performed for untargeted metabolite profiling and MS/MS fragmentation analysis was performed for selected compounds. Further, the barcoding analysis was executed using plastid loci, rpoC1 to integrate with metabolite profiling data. Results: The Principal Component Analysis (PCA) of leaf metabolites showed distinct clusters in different species. Through further analysis, we have also identified the qualitative and quantitative status of unique metabolites across the species, and the majority of the selected compounds were annotated. The metabolic fingerprinting and the hierarchical clustering indicated that though the P. deblis and P. virgatus are distantly related to each other, they are closely associated with their metabolic profiling. Similarly, P. myrtifolius and P. urinaria are closely related to each other with their metabolic fingerprints than the genetic alignment. Further, we performed barcoding with rpoC1 across nine Phyllanthus species ( P. acidus, P. amarus, P. debilis, P. emblica, P. virgatus, P. urinaria, P. lawii, P. myrtifolius, and P. reticulatus ). Sequence similarity search in the GenBank database showed rpoC1 barcode loci from nine Phyllanthus species showed significant identity (>97%) with the sequences of various Phyllanthus species. Conclusions: The bioactive metabolites and their abundance can be assigned to specific species thereby serving as a biological signature and indicators for potential therapeutic use. This study identified differential expression of 14 secondary metabolites from nine Phyllanthus species. Alkaloid compound zeatin was found specific to P. virgatus and delphinidin-3-O- β -D-glucoside was not found in P. myrtifolius . Barcoding and phylogenetic analysis showed P. acidus is the most genetically distinct among the groups and the sequence pair between P.emblica-P.reticulatus and P.emblica-P.urinaria showed the least difference. Graphical abstract: Image 1 Highlights: Identified and clustered nine species of Phyllanthus using DNA barcoding and LC-MS untargeted metabolite profiling. The metabolome data exhibited the differences among the metabolites despite phenotype similarity. This study identified differential expression of 14 secondary metabolites from nine Phyllanthus species. Alkaloid compound zeatin was found specific to P. virgatus and delphinidin-3-O- β -D-glucoside not found in P. myrtifolius. The barcoding efficiency of the loci and the similarity index among species was higher in rpoC1.